2020
DOI: 10.1097/sla.0000000000003748
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Minimally Invasive Trans-thoracic Liver Resection to Examine Intervention Description, Governance, and Outcome Reporting of an Innovative Technique

Abstract: IntroductionThe number of laparoscopic liver resections undertaken has increased. However, lesions located postero-superiorly are difficult to access. This may be overcome by the novel use of transthoracic port(s). Methods for the safe and transparent introduction of new and modified surgical procedures are limited and a summary of these issues, for minimally invasive trans thoracic liver resections (MITTLR), is lacking.This study aims to understand and summarize technique description, governance procedures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Furthermore, we also measured direct distances from assumed trocar site to the tumor and the responsible Glissonean pedicle to confirm feasibility of every surgical procedure. However, in a recent meta‐analysis by Pathak et al, 8 they reported that minimally invasive transthoracic liver resection is still in a challenging and developing stage. Therefore, further studies are warranted to define the suitable indications and recommendations for TTA in LLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also measured direct distances from assumed trocar site to the tumor and the responsible Glissonean pedicle to confirm feasibility of every surgical procedure. However, in a recent meta‐analysis by Pathak et al, 8 they reported that minimally invasive transthoracic liver resection is still in a challenging and developing stage. Therefore, further studies are warranted to define the suitable indications and recommendations for TTA in LLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews have demonstrated that outcome reporting in studies of innovative surgical procedures and devices focuses on short-term, clinical and technical outcomes. 21 22 These outcomes are critical to assess in any early-phase study and are required for US FDA and the UK Medicines and Healthcare products Regulatory Agency approval. 23 24 These types of outcomes are also the recommended focus of early-phase studies (stages 1 and 2) in the IDEAL framework for the introduction and evaluation of new surgical procedures, and devices (IDEAL-D).…”
Section: Discussionmentioning
confidence: 99%
“…27 Our work has explored the complexities surrounding the introduction of new procedures/devices into routine practice, highlighting shortcomings and inconsistencies in how surgical innovation is evaluated and reported. 21 22 28 This has highlighted the need for consensus on the outcomes that are essential to measure to support the safe and efficient introduction and evaluation of new surgical procedures and devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations